Penerapan Teknik Expository dalam Penyutradaraan Film Dokumenter “Museum Perkebunan Indonesia” Karya Fabio Fahrezi Canavaro - Pratiwi Pratiwi; Dani Manesah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The documentary film "Museum Perkebunan Indonesia" by Fabio Fahrezi Canavaro uses the expository technique to present the history of plantations in Indonesia in a factual and educational manner. This technique emphasizes the clear delivery of information through authoritative narration, visual archives, and expert interviews, providing the audience with a deeper understanding. The documentary is structured in a chronological narrative, starting with the early history of plantations during the colonial era, the post-independence developments, and the relevance of plantations in the modern era. Observations of the film reveal the use of visual archives, such as old plantation photos, historical documents, and colonial maps, as well as interviews with historians and plantation practitioners, enriching the narrative. The combination of clear verbal narration and visual evidence strengthens the presented information, making it easier to comprehend. The expository technique successfully changes the perception of plantation history, which was previously considered monotonous, into something more engaging and relevant. This documentary not only serves as a medium for historical education but also provides a fresh perspective on the role of plantations as a key pillar of Indonesia’s economy. Through this approach, the film serves as an effective example of expository technique in historical documentary filmmaking in Indonesia, encouraging the audience to explore often-overlooked history.